DAMPAK PENGGUNAAN VIDEO INTERAKTIF DALAM PEMBELAJARAN KOOPERATIF BERBASIS MASALAH TERHADAP KETERAMPILAN KOLABORASI DAN PEMECAHAN MASALAH SISWA SMP - Sinulingga, Silvia Putriani; mardiati; Sitepu, Dewi Rulia (UIR Press, 2026)
This study to analyze the impact of using interactive videos in Problem-Based Cooperative Learning on students’ collaborative skills and mathematical problem-solving abilities. The research employed a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 60 eighth-grade students of SMP Negeri 11 Binjai, divided into two groups: an experimental class and a control class. The instruments included a mathematical problem-solving test and a collaborative skill observation sheet. Data were analyzed using the t-test and Mann–Whitney U test. The results showed a significant difference in mathematical problem-solving ability between the experimental and control classes. Meanwhile, students' collaboration skills showed no significant improvement. Overall, the findings indicate that Problem-Based Cooperative Learning assisted by interactive videos is effective in enhancing students’ critical thinking, collaboration, and mathematical problem-solving skills. This model is relevant to 21st-century education, which emphasizes the integration of technology, social interaction, and higher-order thinking skills.